دراسة تجريبية لكفاءة المجفف الشمسي ذو الماص المقلوب تحت شروط طقس مدينة الوادي - سماح, بوحنية; هالة, يمبعي (My University, 2022)
تعتبر ألشسمس مصسدر طاقة نظيف ومتجسدد، لذى وجسب إسستغللها في عسدة مجسالت لغرض أدأء وكفاءة ألمجفف ألشمسسي ذو ألمساص ألمقلوب تحست ظسروف تشسغيل حقيقة في جامعسة ألوأدي- ألتقليل من مصادر ألطاقة ألحفورية ألتقليدية. في هذأ ألعمل، تمت درأسة ميدأنية ألهدف منها تحسين وذلك بإدخال موأد حافظة وخازنة للحرأرة )ألحصى ألسود وألكربون ألمنشط ( على مستوي غرفة وجودة ألبطاطا ألمجففة، كما تم وضع ألمجفف على محور دوأرلستقبال أقصى شدة للشعاع. ألتجفيف، كما تم عسزل هسذه ألخسيرة بمادة بوليسسترين عسن ألوسسط ألخسارجي لحفظ ضسسياع ألحسرأرة تم ألعمل ألتجريبي في يوم تميز بإشعاع شمسي معتبر) 14ماي 2022 ، )وبإتباع جملة من ألخطوأت ألتجريب للحصسول على أفضسل ألنتائج، حيث كانت نتائج عمل ألمجفف ألمحسن مرضسية ومقبولة خاصة دور ألموأد ألخازنة للحرأرة في ألحفاظ وإعادة بعث ألحرأرة في وقت إنخفاض شدةThe solar is a renewable energy source, which must be exploited in several areas for the purpose of reducing traditional energy sources. In this work, a study was conducted aimed to improve the thermal performance of the inverted absorber solar dryer under real climatic conditions )El-Oued University(. The solar dryer integrated with energy storage materials )Gravel Black and Activated Carbon( in the drying room, and the latter was isolated with polystyrene to preserve the heat loss and the quality of the dried potatoes. As well, the dryer was placed on a controlling angle arm to receive the maximum intensity of radiation. The experimental work was carried out on a day characterized by significant solar radiation )14 May 2022( for obtained the best results. The results of the study of the improved dryer were satisfactory and acceptable, especially the role of heat-storage materials in preserving and re-emitting heat at a time of low solar intensity. The potato material was completely dried within 5 to 6 hours, and about 81.71% of the moisture
مذكرة ماستر فيزياء
Keywords: ألشمس، ألمجفف ألشمسي، كفاءة، تعزيز، أدأء.; removed from it. Keywords: Solar Dryer, Performance, Iimprove, Efficiency